Analytical Method for Capped Pile–Soil Interaction considering the Load Action of Soil under the Pile Cap. (24th March 2022) - Luo, Shilin; Liu, Mingquan; Jiang, Jianqing; Aierken, Ailifeila; Chang, Jin; Zhang, Xuewen; Zhang, Rui
Abstract : To study the pile–soil interaction mechanism of capped pile, an analytical method considering the load action of soil under the pile cap is proposed. The shearing displacement method is used to derive the lateral friction of pile body under the pile top load, and the Boussinesq solutions is used to derive the lateral friction of pile body considering the load of soil under the cap. The theoretical expressions of axial force and load-settlement curves are also achieved by means of establishing and solving the equilibrium differential equation of the pile body. Comparison of calculation results with the ordinary pile indicates that soil load under the pile cap reduces the lateral friction value; the influenced depth is about four times of the load action radius. The axial force and the load-settlement curve data are verified by a case history data. The results show that the computed data agree well with the measured data. The proposed method can direct the design of capped pile composite foundations.